Efficacy And Compatibility Of An Innovative In-House Dynamic Liver Hepatocellular Carcinoma Phantom For Magnetic Resonance Imaging Applications - Ahmad, Montaser W. M. Saied (2021)
The present study aims to investigate the phantom properties stability over a period of six weeks in addition to simulate the HCC in a dynamic way. In this study, the liver parenchyma was simulated using three different substances with different concentrations: gelatin (with concentration of 2.5wt%, 4 wt%, and 5 wt%); gelatin-agar samples (gelatin with concentration of 2.5wt%, 4 wt%, and 5 wt%) is mixed with constant agar concentration (1.5wt%) in all gelatin-agar samples, and finally, agarose-wax samples (agarose with concentration of 2.5 wt%, 4.5 wt%, and 6 wt%) is mixed with a constant wax concentration 2.6 wt%.